2015
DOI: 10.3109/13880209.2014.974063
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and scavenging capacity of extracts from different parts ofVismia caulifloraagainst reactive oxygen and nitrogen species

Abstract: Context: Vismia cauliflora A.C.Sm. [Hypericaceae (Clusiaceae)] is a plant from Amazonian forest. It is used by Amerindians to treat dermatosis and inflammatory processes in the skin and has been considered an interesting source of bioactive compounds. Objective: We evaluated the scavenging capacity of extracts from V. cauliflora (leaf, branch, stem bark, flower, and whole fruit) against reactive oxygen (ROS) and nitrogen species (RNS), namely, superoxide radical (O . The identification and the quantification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
4
19
0
4
Order By: Relevance
“…In this study, both parts of the plant showed a remarkable capacity to decrease the neutrophils' oxidative burst as induced by PMA in a concentration-dependent manner (Figure 1a), with IC 50 values lower than 2.1 ± 0.2 mg/mL (Table 1). These results corroborate our previous work, which stem bark and flower extracts of V. cauliflora demonstrated the highest efficiency against some relevant ROS generated in chemical systems (Ribeiro et al, 2014).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…In this study, both parts of the plant showed a remarkable capacity to decrease the neutrophils' oxidative burst as induced by PMA in a concentration-dependent manner (Figure 1a), with IC 50 values lower than 2.1 ± 0.2 mg/mL (Table 1). These results corroborate our previous work, which stem bark and flower extracts of V. cauliflora demonstrated the highest efficiency against some relevant ROS generated in chemical systems (Ribeiro et al, 2014).…”
Section: Resultssupporting
confidence: 82%
“…Stem bark and flower extracts of V. cauliflora clearly demonstrated high capacity to scavenge O À 2 and inhibited the oxidation of MCLA with an IC 50 value below 15 ± 1 mg/mL (Table 1 and Figure 1b). The scavenging capacity of stem bark and flower extracts of V. cauliflora against O À 2 in this cellular model also corroborates the antioxidant efficiency of these extracts, which was reported by Ribeiro et al (2014) in a cell-free system with similar IC 50 values (10.3 and 10.7 mg/mL for stem bark and flower extracts, respectively).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations